Clinical characteristics and risk factors of active bleeding in colonic angiodysplasia among the Taiwanese - Yi-Yen Tsai; Bao-Chung Chen; Yu-Ching Chou; Jung-Chun Lin; Hsuan-Hwai Lin; Hsin-Hung Huang; Tien-Yu Huang (Journal of the Formosan Medical Association, 2019)
Background: Colonic angiodysplasia (AGD) is a common cause of gastrointestinal bleeding. However, information on the characteristics and prevalence of colonic AGD is limited. We determined the clinical features of and risk factors for active bleeding in colonic AGD in a Taiwanese population. Methods: From February 2007 to December 2016, 13,047 patients undergoing 16,760 colonoscopies at the Tri-Service General Hospital were included in this study. Eighty-four patients were diagnosed with AGD. We conducted a retrospective study by analyzing the medical records of these patients. The clinical features and endoscopic findings were evaluated. Furthermore, we distinguished colonic AGD into bleeding and non-bleeding types and identified the risk factors for bleeding in colonic AGD. Results: In our study, the prevalence of colonic AGD was 0.6% among all patients who received colonoscopy. Among patients with colonic AGD, we found that many were aged; in all, 58.3% of patients with colonic AGD were older than 65 years. More than half of the patients had hypertensive cardiovascular disease (53.6%) and the AGD lesions were predominantly located in the left-sided colon (41.7%). We analyzed several factors to identify those associated with bleeding colonic AGD. Our results indicated that age (p < 0.001), hypertension (p = 0.020), atrial fibrillation (p = 0.027), and in-patient status (p = 0.006) were significant factors associated with active bleeding lesions. On multivariate analysis, old age was the only significant risk factor. Conclusion: Angiodysplastic lesions in Taiwanese patients were predominantly identified in the left-sided colon. Old age was an independent risk factor associated with active bleeding in colonic angiodysplasia. Keywords: Colonic angiodysplasia, Bleeding, Risk factor